Differential activity of F-box genes and E3 ligases distinguishes sexual versus apomictic germline specification in Boechera - Zühl, Luise; Volkert, Christopher; Ibberson, David; Schmidt, Anja (The journal of experimental botany, 2019)
Germline specification is the first step during sexual and apomictic plant reproduction, and takes place in the nucellus of the ovule, a specialized domain of the reproductive flower tissues. In each case, a sporophytic cell is determined to form the sexual megaspore mother cell (MMC) or an apomictic initial cell (AIC). These differ in their developmental fates: while the MMC undergoes meiosis, the AIC modifies or omits meiosis to form the female gametophyte. Despite great interest in these distinct developmental processes, little is known about their gene regulatory basis.
Gesehen am 28.01.2020